Revamping email communications: A review of five free email design platforms - Okamoto, Karen (Marketing Libraries Journal, 2024)
This article reviews five free online email design platforms that libraries can use to create visually appealing and engaging email newsletters and other email communications. The five platforms reviewed in this article – Beefree, Mosaico, Smore, Stripo, and Tabular – are assessed according to ease of use, the availability of pre-designed templates, and other features, such as the ability to add collaborators. This review begins with a summary of the library and marketing literature on email communications, including best practices, and ends with a brief overview of email marketing platforms and services.